Über holomorphen Lösungen partieller Differentialgleichungen - Strelitz, S.; Kisielius, J. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ш. И. Стрелиц, И. В. Киселюс. О голоморфных решениях дифференциальных уравнений в частных производных Š. Strelicas, J. Kisielius. Apie diferencialinių lygčių su dalinėmis išvestimis holomorfinius sprendinius